2018
DOI: 10.1111/epi.14480
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ketamine in status epilepticus

Abstract: Status epilepticus (SE) is among the most common neurological emergencies. In refractory SE, due to subcellular maladaptive changes, γ-aminobutyric acidergic drugs are no longer effective, and there is an increase in synaptic N-methyl-d-aspartate (NMDA) receptors. Ketamine (KET) is a noncompetitive N-methyl-d-aspartate receptor antagonist that could be of value in the treatment of refractory SE. The aim was to analyze all published studies on KET in the treatment of SE. A systematic search (PubMed) of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 37 publications
0
38
0
1
Order By: Relevance
“…Inhibition of the negative feedback influencing glutamatergic activity via antagonism of presynaptic glutamate receptor activity results in a proconvulsive effect, while at higher ketamine doses, the glutamatergic effects may be suppressed by saturation of the postsynaptic glutamate receptors . Of interest, ketamine is currently recommended for treatment of refractory status epilepticus in humans . Proconvulsants, such as allyl‐glycine, which inhibits GABA synthesis, or the GABA‐receptor antagonist bicuculline, were routinely used in previous decades to reliably provoke photoconvulsive responses in NHP studies…”
Section: Results: Nonhuman Primate Models Of Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the negative feedback influencing glutamatergic activity via antagonism of presynaptic glutamate receptor activity results in a proconvulsive effect, while at higher ketamine doses, the glutamatergic effects may be suppressed by saturation of the postsynaptic glutamate receptors . Of interest, ketamine is currently recommended for treatment of refractory status epilepticus in humans . Proconvulsants, such as allyl‐glycine, which inhibits GABA synthesis, or the GABA‐receptor antagonist bicuculline, were routinely used in previous decades to reliably provoke photoconvulsive responses in NHP studies…”
Section: Results: Nonhuman Primate Models Of Epilepsymentioning
confidence: 99%
“…24 Of interest, ketamine is currently recommended for treatment of refractory status epilepticus in humans. 25 Proconvulsants, such as allyl-glycine, which inhibits GABA synthesis, or the GABA-receptor antagonist bicuculline, were routinely used in previous decades to reliably provoke photoconvulsive responses in NHP studies. 6,11,12…”
Section: The Study Of Potential Seizure Therapies In Baboons (Papiomentioning
confidence: 99%
“…21 Additionally, a case study documented perampanel administration for treatment of Lance-Adams syndrome, resulting in myoclonic seizure suppression. 33 Inaretrospectivestudy of (S)-ketamine treatment for RSE and SRSE, after a median of three failed AEDs, (S)-ketamine was the final drug administered before SEcessationin27(64.3%)patients;however,four(14.8%)ofthese were also receiving propofol concurrently. Across three retrospective reviews, off-label ketamine use resulted in terminationof22.0%ofRSEcases(N=82).…”
Section: Discussionmentioning
confidence: 99%
“…Across three retrospective reviews, off-label ketamine use resulted in terminationof22.0%ofRSEcases(N=82). 33 InareportoffivepatientswithSRSE, stiripentol treatment after failure of 5-8 AEDs was followed by SE cessationinthree(60.0%)patientswithin4daysofadministration. 34 A review of all published studies of ketamine treatment for SE found that 153 (73.9%) adult patients were responders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation